1970
DOI: 10.1021/ja00723a001
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectra and reaction kinetics of NO2, N2O3, and N2O4 in aqueous solution

Abstract: The flash photolysis of N02ions in aqueous solution gives rise to three transient absorptions assigned to N02 (Xmax ~400 nm), N204 (Xmax ~340 nm), and N203 (Xmax <250 nm). The formation of Or in air-saturated alkaline solutions of nitrite ions, and of Br2~and C03 ~radicals in the presence of Br~and C032ions, indicates that O-(or OH) radicals are produced by the primary photolytic process NOr + hv~* NO + O-. The mechanism proposed for the generation of the other nitrogen oxides, 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(123 citation statements)
references
References 0 publications
7
114
1
Order By: Relevance
“…One notes again that the induction time for detection of this oxidant was ∼2 h shorter for the CRL-2278 cells, consistent with its generation by induced O 2 -consuming enzymatic systems other than iNOS and COX-2. This oxidant was stable, as was established by separating the supernatant medium from the cells prior to applying the Amplex® Red/HRP assay; this demonstration excludes the possibility that the oxidant was NO 2 · or peroxynitrite-derived oxidants, which are very short-lived under the experimental conditions (t 1/2 < 10 s) (20,48,61). The oxidant is most likely H 2 O 2 , given its membrane permeability (62,63) and the high selectivity (64) of HRP for this peroxide.…”
Section: (B) Superoxide Generation-immediately Following Activation Omentioning
confidence: 81%
See 1 more Smart Citation
“…One notes again that the induction time for detection of this oxidant was ∼2 h shorter for the CRL-2278 cells, consistent with its generation by induced O 2 -consuming enzymatic systems other than iNOS and COX-2. This oxidant was stable, as was established by separating the supernatant medium from the cells prior to applying the Amplex® Red/HRP assay; this demonstration excludes the possibility that the oxidant was NO 2 · or peroxynitrite-derived oxidants, which are very short-lived under the experimental conditions (t 1/2 < 10 s) (20,48,61). The oxidant is most likely H 2 O 2 , given its membrane permeability (62,63) and the high selectivity (64) of HRP for this peroxide.…”
Section: (B) Superoxide Generation-immediately Following Activation Omentioning
confidence: 81%
“…Sequential induction of LOX, iNOS, and COX-2 could lead to development of bactericidal potential within the cell by arginine and lipid autoxidation to generate NO 2 · in the manner suggested in Scheme 1. In this hypothetical scheme, (1) LOX functions to generate lipid hydroperoxides from reaction of O 2 with endogenous lipids (72) for (2) activation of and use by COX-2 (71) in reactions with NO 2 -(3) formed by iNOS-catalyzed arginine oxidation by O 2 (52) and subsequent aerobic oxidation of NO · (61). Recent studies have revealed a complex interaction between iNOS and COX-2, which may involve physical association of the two enzymes (73), COX-2 catalyzed consumption of NO · (16), modification of COX-2 activity via S-nitrosylation (73), and possibly inactivation of COX-2 by radical coupling of its essential tyrosyl radical with iNOS-generated NO · (74).…”
Section: Physiological Implicationsmentioning
confidence: 99%
“…3, which were obtained from fast flow mixing of bicarbonate and peroxynitrite solutions as described in the legend to the figure. nitrite (reaction 9) (33)(34)(35). Under the same conditions as shown in Fig.…”
Section: Table I Epr Parameters Of the Carbonate Radical In Various Mmentioning
confidence: 96%
“…Calibration curves were constructed using solutions of NaNO 2 of known concentrations (2-50 nM) in bidistilled water. The concentration of the stock solution was controlled assuming the coefficient of molar absorption of nitrite to be 2,400 M −1 cm −1 at 230 nm [24].…”
Section: Determination Of Nitrite By Means Of 23-diaminonaphthalene mentioning
confidence: 99%